Pengaruh Asimetri Informasi dan Ukuran Perusahaan Pada Income Smoothing Dengan GCG Sebagai Variabel Moderasi - Apriani, Ni Wayan Lia; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
This study aims to determine empirically the effect of asymmetry of information and the size of the company on income smoothing with good corporate governance as a moderating variable. This study was conducted on companies listed on the Indonesia Stock Exchange and included in the CGPI index rating during the observation period, ie 2010-2015. Methods of data collection using non-participant observation method. This research uses logistic analysis technique with interaction test. The results of data analysis in this study indicate that information asymmetry has a positive effect on income smoothing while firm size has a negative effect on income smoothing. Good corporate governance variables are not moderate the influence of information asymmetry on income smoothing. Good corporate governance is also unable to moderate the effect of firm size on income smoothing. This research can also be used as consideration of investor in making decision.   Keywords: income smoothing, information asymmetry, firm size and good corporate governance.